KUDOS: Have some good news to share about yourself or a colleague? Send your announcements to business@CITIZEN-TIMES.com with "Kudos" in the subject line. We will run your submissions as soon as possible and in the order in which they were received (Asheville Citizen - Times, 2007)
McCracken was formerly the club's corporate wellness director. Since 1975, the Asheville Racquet and Fitness Club has operated at 200 Racquet Club Road, off Hendersonville Road in south Asheville.